Pemerolehan bahasa aspek fonologi pada anak usia 2 Tahun - Harahap, Nadiyah Iklimah; Qolbi, Mauritsa Fitriyah; Putra, Dona Aji Karunia (Universitas Lampung, 2024)
This study aims to describe language acquisition in children aged 2 years and 2 months in terms of phonological aspects. This research was conducted using a qualitative descriptive method. The subject in this study was a child aged 2 years 2 months, male and with the initials MFA. The data in the research are speech produced by children aged 2 years and 2 months. The data collection techniques applied in this research are observation and documentation. The results showed that MFA subjects were able to pronounce vowels in front-high /i/, front-middle /e/, high-back /u/, middle-middle /ǝ/, middle-low /a/ and back-middle /o /, but has difficulty pronouncing vowels such as /u/ and /e/ in word-final position. Regarding consonant phonemes, there are several phonemes that the subject cannot pronounce correctly, such as the consonants /b/, /c/, /h/, /k/, /l/, /p/, /r/, /s/ and /t/ especially in word initial position. The strategy applied by the subject to overcome these difficulties is phoneme deletion and substitution.Keywords: Language Acquisition, Phonological Aspects, and 2 Years Old Child